Malignant pleural mesothelioma in a child - Jed Brendan Scharf; Gordon Mitchell Lees; Consolato Maria Sergi (Elsevier, 2015)
Malignant pleural mesothelioma (MPM) is an aggressive malignancy that occurs extremely rarely in the pediatric population. It carries a dismal prognosis. Adult studies are often used to guide therapy in the pediatric population, as a limited number of case reports form the body of pediatric literature. Herein, we document the course and treatment of an 8-year old male diagnosed with MPM. The diagnosis came after he presented to his family physician with dyspnea and was found to have a large right-sided chest mass on subsequent imaging. Through an initial right pneumonectomy and subsequent chest wall excision, followed by chemotherapy with Pemetrexed and Cisplatin he remains virtually disease free today, almost 2 years following surgery.